ANALISIS ROA DAN ROE TERHADAP NILAI PERUSAHAAN DENGAN CORPORATE SOCIAL RESPONSIBILITY SEBAGAI VARIABEL MODERATING (Studi Pada Perusahaan BUMN yang Terdaftar di BEI Periode 2010-2013) - Wahyuningsih, Panca; Widowati, Maduretno (JURNAL STIE SEMARANG, 2016)
The purpose of financial management is to maximize the wealth of shareholders, which means increasing the value of the company, this is a measure of objective value by the public and the orientation of the company's survival, the company can take measurements of financial performance of the financial statements at the end of the period. In measuring the financial performance, financial ratios are frequently used profitability ratios, such as return on assets (ROA) and Return On Equity (ROE), while Corporate Social Responsibility (CSR) as part of a strategy to increase the value of companies that allegedly provided a more powerful influence , because it is based on the social impact of transparency on the activity or activities undertaken by the company This study aims to determine the effect of financial performance (ROA and ROE) to the value of companies with Corporate Social Responsibility (CSR) as a moderating variable. While in general is to test, analyze whether the ROA and ROE affect the value of the company, with moderated CSR. Thus it can be seen Which more dominant influence between the ROA or ROE to company value and whether the variable CSR can serve as a moderate. Results are expected to provide us with feedback to the management of state-owned enterprises listed on the Stock Exchange, in terms of increasing the value of the company. Methods of data analysis using multiple regression analysis to test the hypothesis. The population in this study is state-owned enterprises listed on the Indonesia Stock Exchange Period 2010-2013. The sample in this research was determined by purposive sampling, in order to obtain as much data as 68 companies.Variables in this study consisted of four variables, ROA, ROE becomes the independent variable and CSR moderating variable, while the value of the company becomes the dependent variable.